Comparative Study of the Effects of Continuous Positive Airway Pressure and Nasal High-Flow Therapy on Diaphragmatic Dimensions in Preterm Infants - El-Mogy, Mohamed; El-Halaby, Hanan; Attia, Gehan; Abdel-Hady, Hesham (American Journal of Perinatology, 2018)
Objective Nasal continuous positive airway pressure (nCPAP) and nasal high-flow therapy (nHFT) are the most common forms of noninvasive respiratory support in preterm infants. We conducted this study to compare effects of nCPAP and nHFT on diaphragmatic dimensions as assessed by bedside ultrasonography in preterm infants.Study Design A prospective, randomized crossover study comprised 24 preterm infants. Group 1 (n = 12): started on nCPAP for 60 minutes and then switched to nHFT for 60 minutes. Group 2 (n = 12): started on nHFT for 60 minutes then switched to nCPAP for 60 minutes. Ultrasonographic assessment of diaphragmatic dimensions was performed at the end of each epoch.Results There were no statistically significant differences in diaphragmatic dimensions at the end of each epoch of nCPAP or nHFT. The diaphragm thickening fraction (DTF) was not significantly different with either nCPAP or nHFT [23.4 (13.7–28.0) versus 23.4 (11.2–31.6), p = 0.57]. No significant differences were found regarding heart rate, respiratory rate, Silverman–Anderson scores, and SpO2 on nCPAP and nHFT. All infants enrolled tolerated the crossover maneuver.Conclusion Stable preterm infants (30.3 ± 2.2 weeks' gestation) with mild respiratory dysfunction show comparable effects on diaphragm thickness and excursion during relatively brief periods of support on nCPAP or nHFT.Clinical Trial Registration Registry name: Clinical Trials.gov. Registration number: NCT02421328. Web link to study on registry: https://clinicaltrials.gov/ct2/show/NCT02421328.
Keywords: CPAP; nHFT; preterm; diaphragm; ultrasound